2012
DOI: 10.1016/s1995-7645(12)60029-7
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro cytotoxic activity of β-Sitosterol triacontenate isolated from Capparis decidua (Forsk.) Edgew

Abstract: The data therefore provide direct evidence for the role of β-Sitosterol triacontenate as a potent antimetastatic agent, which can markedly inhibit the metastatic and invasive capacity of malignant cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The non significant effect of the extract on the albumin and total protein in the serum of animals at all the doses investigated could imply that the synthetic and secretory functions of the liver with respect to these proteins were not affected. Furthermore, the increase in serum total and conjugated bilirubin could indicate mild haemolysis and obstruction in the normal excretion of bile [41][42][43][44][45][46][47][48] . The elevated level of globulin suggests increase in functional activity of the liver with respect to the plasma protein.…”
Section: Discussionmentioning
confidence: 99%
“…The non significant effect of the extract on the albumin and total protein in the serum of animals at all the doses investigated could imply that the synthetic and secretory functions of the liver with respect to these proteins were not affected. Furthermore, the increase in serum total and conjugated bilirubin could indicate mild haemolysis and obstruction in the normal excretion of bile [41][42][43][44][45][46][47][48] . The elevated level of globulin suggests increase in functional activity of the liver with respect to the plasma protein.…”
Section: Discussionmentioning
confidence: 99%
“…Among most common phytosterols, stigmasterol (3β,20R,22E,24S)-stigmasta-5,22-dien-3-ol (5) and β-sitosterol (3β,20R,24R)-stigmast-5-en-3-ol (6) were employed. While the former was already tested against cancer in natural form (Ali et al 2015, Ghosh et al 2011, the latter showed effect on tumor cells in ester form (Rathee et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant chemicals found in many foods are frequently cited as the basis of claims for the benefits of a high intake of vegetables and fruits in the diet [28,29] . In a 2010 survey of 1 000 plants, 356 had clinical trials published evaluating their "pharmacological activities and therapeutic applications" available in the Western market [30,31] . Most thrombolytic agents work by activating the enzyme plasminogen, which clears the cross-linked fibrin mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Adiantum philippense L. (A. philippense) (Family-Adiantaceae) locally known as Goyalelata, is a small fern. Stipes 10-15 cm long, tufted, naked, wiry, polished dark chestnut-brown; fronds [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] cm long and 7.6 cm broad, simply pinnate, often elongated and rooting at the apex; pinnae subdimidiate, the lower edge nearly in a line or oblique with the petiole, the upper edge rounded.…”
Section: Introductionmentioning
confidence: 99%